2007
DOI: 10.5194/acp-7-3261-2007
|View full text |Cite
|
Sign up to set email alerts
|

Validation of MIPAS-ENVISAT NO<sub>2</sub> operational data

Abstract: The comparison to ACE satellite observations exhibits only a small negative bias of MIPAS which appears not to be significant. The independent satellite instruments HALOE, SAGE II, and POAM III confirm in common for the spring-summer time period a negative bias of MIPAS in the Arctic and a positive bias in the Antarctic middle and upper stratosphere exceeding frequently the combined systematic error limits. In contrast to the ESA operational processor, the IMK/IAA retrieval code allows accurate inference of NO… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 74 publications
(80 reference statements)
4
45
0
1
Order By: Relevance
“…During day, NO 2 reacts rapidly to reform NO either by reaction with atomic oxygen (upper stratosphere) or photolysis: Wetzel et al, 2007;Kerzenmacher et al, 2008;Wolff et al, 2008). In this paper we focus on Arctic stratospheric mixing ratios of chlorine and nitrogen species which change quickly their concentration around the terminator between night and day.…”
Section: G Wetzel Et Al: Diurnal Variations Of Reactive Chlorine Anmentioning
confidence: 99%
“…During day, NO 2 reacts rapidly to reform NO either by reaction with atomic oxygen (upper stratosphere) or photolysis: Wetzel et al, 2007;Kerzenmacher et al, 2008;Wolff et al, 2008). In this paper we focus on Arctic stratospheric mixing ratios of chlorine and nitrogen species which change quickly their concentration around the terminator between night and day.…”
Section: G Wetzel Et Al: Diurnal Variations Of Reactive Chlorine Anmentioning
confidence: 99%
“…A flight of the balloon version of the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS-B) instrument was carried out from Kiruna (Sweden,68 • N) on 20/21 March 2003 as part of a validation campaign for the chemistry instruments MIPAS, GOMOS, and SCIAMACHY aboard the environmental satellite ENVISAT (see, e.g., Wetzel et al, 2007). Owing to the long duration of this flight, a good match with observations of the Improved Limb Atmospheric Spectrometer (ILAS)-II sensor aboard the ADEOS-II satellite could be managed.…”
Section: Introductionmentioning
confidence: 99%
“…Similar approaches have been used before in other studies, e.g. Bracher et al (2005), , Wetzel et al (2007), Brohede et al (2007a), and Wolff et al (2008).…”
Section: Diurnal Scalingmentioning
confidence: 92%
“…It was found that the two NO x data sets typically agreed within 20 % between 25 and 50 km. Wetzel et al (2007) found that, in the mid-stratospheric MIPAS ESA version 4.6 NO 2 , diurnally scaled using data from a 1-D photochemical model agreed best with balloon-borne measurements, with biases typically better than 10 %. In similar comparisons with correlative satellite-based solar occultation measurements, the MIPAS ESA profiles typically agreed within 10-30 %.…”
Section: Mipasmentioning
confidence: 96%